HUBUNGAN SENAM AEROBIK LOW IMPACT DENGAN PENURUNAN BERAT BADAN PADA AKSEPTOR KB SUNTIK 3 BULAN DI DESA PANCA MAKMUR: Relationship With Low Impact Aerobic Gymnastics Weight Loss In 3-Month Injection KB Accepters In Panca Makmur Village - Rapi, Desi (LPPM - STIKES Pemkab Jombang, 2024)
Low impact aerobics is aerobic exercise that is carried out in a light way (light impact), the movements do not require strength and violence and are relatively slower to follow the rhythm of the music. Aerobic exercise with moderate to high intensity can burn fat ranging from 500 to 800 times each exercise with a duration of 30 to 60 minutes. The purpose of this study was to analyze the relationship between low impact aerobic exercise and weight loss in 3-month injection family planning acceptors in Panca Makmur Village. This research was conducted using the correlation analytic research method. The population is KB injection acceptors of 100 people with a sample of 50 taken by purposive sampling technique. Statistical test using the chi square test. The results showed that most of the respondents did low impact aerobics routinely as many as 29 people (58%), did low impact aerobics routinely as many as 29 people (58%) and there was a relationship between low impact aerobics and weight loss injectable birth control acceptors. 3 months in Panca Makmur Village with a p value of 0.000. It is hoped that the results of the research can be used as evaluation material for 3-month injection family planning acceptors to diligently control their weight and carry out routine low impact aerobic exercise and work together with health agencies in running aerobic exercise programs.